2020
DOI: 10.1002/jsid.956
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intermolecular interactions on the formation of spontaneous orientation polarization in organic semiconducting films

Abstract: Spontaneous orientation polarization (SOP) has been frequently observed in the evaporated films of organic light‐emitting diode materials. Because SOP modifies the charge injection and the accumulation properties of the device, understanding and controlling SOP is crucial in optimizing the performance of the device. In this study, we investigated the dominant factors for SOP formation by focusing on intermolecular interactions. We examined the giant surface potential characteristics of coevaporated films incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 22 publications
5
45
0
Order By: Relevance
“…We measured the surface potential characteristics of the coevaporated films and found that the molecular orientation of TPBi was enhanced even in the UGH‐2 host, though the apparent enhancement factor was smaller than that in the CBP host. The enhancement of the molecular orientation is attributed to the reduction of the PDM interaction between TPBi molecules, which deteriorates SOP as previously reported 11 . In addition, our results suggest that the SOP of TPBi is robust even in the UGH‐2 host molecules with a weak vdW interaction compared to polyhedral shaped molecules like Ir complexes.…”
Section: Introductionsupporting
confidence: 83%
See 4 more Smart Citations
“…We measured the surface potential characteristics of the coevaporated films and found that the molecular orientation of TPBi was enhanced even in the UGH‐2 host, though the apparent enhancement factor was smaller than that in the CBP host. The enhancement of the molecular orientation is attributed to the reduction of the PDM interaction between TPBi molecules, which deteriorates SOP as previously reported 11 . In addition, our results suggest that the SOP of TPBi is robust even in the UGH‐2 host molecules with a weak vdW interaction compared to polyhedral shaped molecules like Ir complexes.…”
Section: Introductionsupporting
confidence: 83%
“…As shown in Figure 2A, all the films exhibited typical GSP behavior; that is, the surface potential induced in the films was proportional to the film thickness 3,5 . The surface potential data of the TPBi neat and TPBi:CBP coevaporated films are adapted from Noguchi et al 10 The GSP slope of the pristine (TPBi neat) film (Δ TP ) was estimated to be 63.1 mV/nm, and that of the coevaporated films with CBP (Δ TC ) and UGH‐2 (Δ TU ) was 67.4 and 44.5 mV/nm, respectively. Δ TC is larger than Δ TP despite the half PDM density, which indicates that the degree of orientation of PDM in TPBi was enhanced in the coevaporated film.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations